If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1y + 0x = 4 Anything times zero is zero. 1y + 0x = 4 Reorder the terms: 0 + 1y = 4 Remove the zero: 1y = 4 Solving 1y = 4 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '1'. y = 4 Simplifying y = 4
| 0.2x+7.3=6.4 | | (2x+-3)*x=54 | | 9(0)+7x=63 | | 8.65x-6.5=-34.04+13.75x | | 16a=80 | | 3x^3+11x^2-15x+16*3x+2= | | -2=3f-5 | | 4x+2y=6x+12 | | 9(0)+7x^2=63 | | 5(y-6)-16=-11 | | 35*7=(X*7)+(5*7) | | 3=12+k | | 8(8)(-7)(-6)= | | 2a+ab=18 | | x=4x^2-25 | | 22.5x-15=120 | | 6-15-(-9)= | | b-10=15 | | 9x^1+7x^2=63 | | 0.5m+15=0.25m+25 | | 3x=8-8 | | 3.5-5=x | | 6b+14=3b-21 | | X=2y+4y+1 | | 0.5m+15=0.25+25 | | x+16=7+4x | | -6+(-7)+16+(-5)= | | -6(6x-6)+(4x-8)= | | 5(x+2)=3(x+3) | | -2(2t+3)=-14 | | 2y+6x=-10 | | 0=20x^2+27x-8 |